Synthesis, spectroscopic characterization, crystal structure and pharmacological properties of some novel thiophene-thiourea core derivatives - Saeed, Sohail; Rashid, Naghmana; Ali, Muhammad; Hussain, Rizwan; Jones, Peter G. (European Journal of Chemistry, 2010)
This article presents our research concerning the synthesis of new thiophene-thiourea derivatives (1-12) and their pharmacological properties. These novel thiophene-thiourea derivatives were synthesized and characterized by IR, 1H and 13C NMR spectroscopy, mass spectrometry and elemental analysis. The crystal structure of N,N-diphenyl-N’-(thiophene-2-carbonyl)-thiourea was determined from single crystal X-ray diffraction data. It crystallizes in the monoclinic space group P21 with unit cell dimensions of a=11.7469(5) Å, b=6.0849(2) Å, c=12.5792(6) Å, β= 117.736(7) ° and V = 795.8(6) Å3. The mass fragmentation pattern has also been discussed. The synthesized compounds were screened for their in vitro antifungal activities against the standard strains: C. Albicans, C. Glabrata, and C. Tropicalis. The compounds N-thiophene-N’,N’-bis(dimethyl-phosphinoylmethyl)thiourea, N-[(4-nitro-1H-imidazol-2-yl)carbamothioyl]thiophene-2-carboxamide and N,N-diethyl-N’-(thiophene-2-carbonyl)-thiourea showed significant antifungal activities against microbial species.